Efektivitas Metode PjBL terhadap Hasil Belajar pada Mata Pelajaran Tarikh Siswa SMA Muhammadiyah 3 Surakarta: The Effectiveness of the PjBL Method on Learning Outcomes in the Subject of Tarikh for Students of SMA Muhammadiyah 3 Surakarta - Lukita Paramita; Iffah Mukhlisah; Siti Fathiyatus Sholihah (ITScience (Information Technology and Science), 2025)
This study aims to evaluate the effectiveness of the Project-Based Learning (PjBL) method in improving student learning outcomes in the subject of Tarikh at SMA Muhammadiyah 3 Surakarta in the 2024/2025 academic year. The background of this study is based on the importance of using a learning model that can increase active student participation, especially in Islamic Religious Education (PAI). This aims to ensure that student understanding is not merely theoretical or relies on memorization, but can be applied in real life. PjBL is appropriate because it focuses on contextual, collaborative, project-based learning and emphasizes problem solving. The approach used is quantitative with a comparative research type. The research sample involved 36 grade XII IPS students selected using purposive sampling. The instruments used were a pre-test and a post-test to measure differences in learning outcomes before and after implementing PjBL. Data analysis was carried out using a paired t-test. The analysis showed a significant increase in student learning outcomes after using the PjBL method, with an average pre-test score of 58.39 and a post-test score of 70.81. A 2-tailed significance value (Sig.) of 0.000 (<0.05) indicates that the increase is statistically significant. Thus, the PjBL method has proven effective in improving learning outcomes while developing critical thinking skills, collaboration, and a deeper understanding of the Tarikh material. This research contributes to developing Islamic Religious Education learning models that are more innovative, interactive, and in line with the demands of learning in the 21st century.